Analysis of Different Approaches for Clinical Cochlear Coverage Evaluation After Cochlear Implantation. Issue 8 (September 2018) - Schurzig, Daniel; Timm, Max Eike; Batsoulis, Cornelia; John, Samuel; Lenarz, Thomas
Abstract : Hypothesis: Methods for cochlear coverage determination vary in their accuracy and are hence not equally reliable. Background: The audiological outcome after cochlear implantation is known to depend on several factors. One factor shown to positively correlate with speech perception is the insertion angle. This parameter is one of the ways to describe the fraction of the cochlea spiral exposed to electric stimulation after implantation, also known as cochlear coverage, which itself is dependent on the length and type of electrode array as well as the size and shape of the implanted cochlea. While the assessment of cochlear coverage as the insertion angle is quick and uncomplicated, the accuracy of representing the relative fraction of the cochlea exposed to electric stimulation by this single measurement value remains unknown. Methods: Both the cochlea spiral and implanted electrode array of N = 10 cochlear implant patients were traced within clinical imaging data and processed to derive the respective cochlear coverage values. These values were compared to ones derived with alternative measures like the insertion angle as well as other methods to yield the accuracy and reliability of these approaches. Results: The insertion angle as well as two novel approaches were found to be superior to all other analyzed assessment options and well suited for clinical cochlear coverage evaluations. Conclusion: Insertion angle measurements are well suited for cochlear coverage determination, especially regarding retrospective analyses. Prospective studies independent of anatomical irregularities should be performed with the newly proposed approaches.